1998
DOI: 10.1002/(sici)1521-3803(199812)42:06<416::aid-food416>3.3.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Heat and storage effects on the flavour of peanuts

Abstract: Two peanut varieties, Giza 4 and Giza 5 were subjected to different heat treatments such as drying in solar drier at air speed 0.5 and 2 m/sec with average temperature 45 and 60 degrees C and heating in oven at 120 and 150 degrees C. The sensory evaluation of the two varieties showed insignificant differences among varieties and heating processes. A correlation between the sensory and instrumental data was found. The high sensory scores of samples heated at 150 degrees C were attributed to the presence of high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Firstly, the variety of common beans used ( kabulangeti ) has a dark skin and upon cooking results in very dark grey broth. Secondly, Maillard reaction products, such as furans and sulfur‐containing compounds, may result from high‐temperature, low‐moisture extrusion cooking,28 though these volatile products may also enhance flavour in thermally processed products 29. Thirdly, the vitamin–mineral premix used for fortification in this study had a grey colour and may have exacerbated colour deterioration.…”
Section: Resultsmentioning
confidence: 82%
“…Firstly, the variety of common beans used ( kabulangeti ) has a dark skin and upon cooking results in very dark grey broth. Secondly, Maillard reaction products, such as furans and sulfur‐containing compounds, may result from high‐temperature, low‐moisture extrusion cooking,28 though these volatile products may also enhance flavour in thermally processed products 29. Thirdly, the vitamin–mineral premix used for fortification in this study had a grey colour and may have exacerbated colour deterioration.…”
Section: Resultsmentioning
confidence: 82%
“…Since then thousands of publications have documented this reaction during thermal processes (i.e. roasting and cooking) of foods and in human disease and aging . The well‐documented chemical modification of the amino acid side chains of proteins in foods during cooking begins with formation of a Shiff's base linkage of an aldehyde group of a reducing sugar with the alpha or epsilon amino groups of proteins, which then undergo Amadori rearrangement to form stable ketoamine derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…This was also expected, since the production of secondary oxidation products will be most pronounced at longer storage times. This is in accordance with a study on the storage stability of roasted peanuts were they also found a larger production of secondary oxidation products at later storage times (El-Kayati, Fadel, Abdel Mageed, & Farghal, 1998). The plot furthermore reveals that pyrazines and pyridines are present in the highest amounts when samples are stored in darkness compared to light, while samples stored in light contain the largest concentrations of most of the identified esters and furans.…”
Section: Secondary Oxidation Products -Dynamic Headspace Gc-msmentioning
confidence: 99%